2010
DOI: 10.1097/iae.0b013e3181dde612
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and Efficacy of Passive Removal of Silicone Oil With 23-Gauge Transconjunctival Sutureless System

Abstract: Passive removal of silicone oil with 23-G transconjunctival sutureless system may hasten postoperative recovery by decreasing overall surgical time and postoperative inflammation. It is a safe and effective procedure when compared with 20-G active silicone oil removal for 1000 centistoke oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…There have only been a few reports in the literature describing sutureless removal of silicone oil. 11,28,29 To the best of our knowledge, this is the first study to compare the safety and efficacy of silicone oil removal using the 25-gauge vitrectomy system with the 20-gauge vitrectomy system. Our study showed that the removal of silicone oil through the 25-gauge cannula is safe and effective.…”
Section: Discussionmentioning
confidence: 98%
“…There have only been a few reports in the literature describing sutureless removal of silicone oil. 11,28,29 To the best of our knowledge, this is the first study to compare the safety and efficacy of silicone oil removal using the 25-gauge vitrectomy system with the 20-gauge vitrectomy system. Our study showed that the removal of silicone oil through the 25-gauge cannula is safe and effective.…”
Section: Discussionmentioning
confidence: 98%
“…The main benefits of small incisions are that they generally do not require suturing, they prevent adhesions from repeated operations, and they provide a short operating time, minimal trauma, less irritation, comfortable surgery and speedy recovery. 9 , 10 , 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…SOR can be performed with 20-gauge (G), 23-G or 25-G extraction cannulae. 9 , 10 , 11 In recent years, smaller gauge sclerotomies have become a preferred technique in SOR. 9 , 10 , 11 The main advantages of small-gauge sclerotomies are their self-sealing properties, early incision healing, low ocular surface irritation and more cosmetically satisfying results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eyes that had 23-G port creation had significantly less ocular surface inflammation compared to the 20-G group. [72]…”
Section: Introductionmentioning
confidence: 99%